CLIMATE CHANGE AND FOOD PRODUCTION: INVESTIGATING AGRICULTURE-INDUCED GREENHOUSE GAS EMISSIONS IN NIGERIA - ABBAH, EMMANUEL UMALE; DOKI , NAOMI ONYEJE; JEROME, TERHEMBA ANDOHOL (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This research investigated the effect of agriculture-induced greenhouse gas emissions on food production in Nigeria from 1981 to 2022. The Auto-regressive Distributed Lag (ARDL) methodology is employed. Findings revealed that agriculture-induced greenhouse gas emission negatively affected food production during the period of the study, however, its effect is found to be insignificant. The rise in the magnitude of agriculture-induced greenhouse gas emission from 7% to 20% in the short-term and long-term respectively is an indication that agriculture induced greenhouse gas emission portends great danger towards the achievement of adequate food production in Nigeria. The result of the findings also implies that the status of the agricultural sector as the highest emitter of greenhouse gas emissions in Nigeria does not necessarily transmit to making its negative impact on food production significant. Thus, this research recommends the training of farmers through workshops and agricultural extension services to practice climate-smart agriculture to ensure that greenhouse gas emission from agriculture is minimized and to reverse this negative trend possibly. The elimination of bush burning and deforestation, the use of organic manure as against synthetic fertilizers, the practice of irrigation farming, and modern livestock practices (ranching) should be encouraged among farmers by the government both at the Federal, State, and Local government levels through the various established agricultural ministries and agencies in the country.